Real world SOF/VEL/VOX retreatment outcomes and viral resistance analysis for HCV patients with prior failure to DAA therapy. Issue 9 (8th June 2021) - Smith, David A.; Bradshaw, Daniel; Mbisa, Jean L; Manso, Carmen F.; Bibby, David F; Singer, Joshua B; Thomson, Emma C; da Silva Filipe, Ana; Aranday‐Cortes, Elihu; Ansari, M. Azim; Brown, Anthony; Hudson, Emma; et al.
Abstract: Sustained viral response (SVR) rates for direct‐acting antiviral (DAA) therapy for hepatitis C virus (HCV) infection routinely exceed 95%. However, a small number of patients require retreatment. Sofosbuvir, velpatasvir and voxilaprevir (SOF/VEL/VOX) is a potent DAA combination primarily used for the retreatment of patients who failed by DAA therapies. Here we evaluate retreatment outcomes and the effects of resistance‐associated substitutions (RAS) in a real‐world cohort, including a large number of genotype (GT)3 infected patients. 144 patients from the UK were retreated with SOF/VEL/VOX following virologic failure with first‐line DAA treatment regimens. Full‐length HCV genome sequencing was performed prior to retreatment with SOF/VEL/VOX. HCV subtypes were assigned and RAS relevant to each genotype were identified. GT1a and GT3a each made up 38% (GT1a n = 55, GT3a n = 54) of the cohort. 40% ( n = 58) of patients had liver cirrhosis of whom 7% ( n = 4) were decompensated, 10% ( n = 14) had hepatocellular carcinoma (HCC) and 8% ( n = 12) had received a liver transplant prior to retreatment. The overall retreatment SVR12 rate was 90% (129/144). On univariate analysis, GT3 infection (50/62; SVR = 81%, p = .009), cirrhosis (47/58; SVR = 81%, p = .01) and prior treatment with SOF/VEL (12/17; SVR = 71%, p = .02) or SOF+DCV (14/19; SVR = 74%, p = .012) were significantly associated with retreatment failure, but existence of pre‐retreatment RAS was not when viral genotype was taken into account. Retreatment with SOF/VEL/VOX is very successful for non‐GT3‐infected patients. However, for GT3‐infected patients, particularly those with cirrhosis and failed by initial SOF/VEL treatment, SVR rates were significantly lower and alternative retreatment regimens should be considered.